제천시 농림어업인 삶의 질 향상 5개년 기본계획 수립 - 박대식 (한국농촌경제연구원, 2005)
The main purpose of this study was to prepare the Jecheon-City's five-year(2005～2009) basic plan to improve rural residents' quality of life, based on related plans. The major research methods of this study were the collection of existing related data, interview, field survey, and others. Descriptive statistics such as frequencies, percentage, and mean were used to organize and summarize the data. In this study, the visions and strategies of rural welfare & education, and regional development policies, the major task of basic plan, the structure and process of basic plan, and investment plans were suggested. The major driving tasks in the rural welfare area were ① expansion of social security network, ② expansion of pubic health and medical service, ③ reinforcement of the welfare assistance for women, infants, and the elderly. The major driving tasks in the rural education area were ① reinforcement of students' education opportunities, ② reduction of educational expenses, ③ improvement of teachers' working condition and improvement of education environment. The major driving tasks in the regional development area were ① reinforcement of human capacity, ② sustainable regional development and improvement of basic living environment. The major driving tasks in the activation of complex industry area were ① assistance for excavation and industrialization of local resources, ② expansion of rural tour base, ③ reservation and development of scenic beauty. Researchers: Dae-Shik Park, Mi-Ryung Song, Sang-Jin Ma,Eun-Jung Shin E-mail Address: pds8382@krei.re.kr